Development of Interpretation for Strengthening Mathematical Thinking Through Worksheets of Learners in Junior High Schools - Iryani, Desy; Bistari, Bistari; Hartoyo, Agung (STKIP Singkawang, 2023)
The purpose of this study was to describe the development of interpretations to strengthen mathematical thinking in comparative material, using worksheets developed for class VII students of SMP Negeri 1 Embaloh Hilir. This study uses a 4D model which consists of 4 stages, namely definition, design, development and dissemination. Students in class VII SMP Negeri 1 Embaloh Hilir are the research subjects. The research results were obtained from each stage of the implementation of development activities using the 4D model with the instrument questions in the LKPD and interviews. The results of research on class VII students of SMP Negeri 1 Embaloh Hilir show that the development of interpretation through LKPD is feasible and can improve mathematical thinking skills. This is shown from the results of the LKPD work which obtained an average of 71.87. Students use interpretation abilities when working on questions in LKPD so that students' mathematical thinking indicators become good.